Overview of air pollution in typical basin of China under the target of carbon neutrality - Li, Xiao Ju; Abdullah, Luqman Chuah; Sobri, Shafreeza; Md Said, Mohamad Syazarudin; Hussain, Siti Aslina; Tan, Poh Aun (Springer, 2021)
Sichuan Basin (SCB) is a typical basin in southwest China and a traditional smog-prone area. Control of air pollution in this area is particularly critical in achieving China’s carbon emission peak and carbon neutral goals. It is characterized by high population density, heavy transportation, rapid industrialization, complex topography, and meteorological conditions. However, the air pollution studies of SCB remain the sparse and in-depth studies are still warranted. None of the previous research has synthetically reviewed the status of air pollution in this region. This paper comprehensively overviewed the air pollution of SCB from five aspects: air pollution characteristics, sources of air pollutants, driving factors of air pollution, air pollution episodes and health risks. A comparison on the air pollution of typical megacities in the basin was also discussed. The findings and shortcomings of the existing studies were also summarized. Recommendations for future research directions were also proposed.